Experimental investigations of boundary layer impact on the airfoil aerodynamic forces of Horizontal Axis Wind Turbine in turbulent inflows. (15th September 2017) - Li, Qing'an; Kamada, Yasunari; Maeda, Takao; Nishida, Yusuke
Abstract: In order to check whether the developed airfoil UMY02-T01-26 can improve aerodynamic performance, a multiport device is used to investigate the pressure distribution acting on a single blade surface under inflow conditions. In this experiment, aerodynamic forces are discussed with different Reynolds numbers of Re = 0.5 × 10 5, 1.0 × 10 5, 1.5 × 10 5 and 2.0 × 10 5 . Furthermore, for the purpose of clarifying the impact of turbulence intensity, the aerodynamic forces characteristics of HAWT airfoil are estimated in the case of different turbulence intensities generated by static turbulence grids. According to the wind tunnel experimental analysis, it can be known that the blade boundary layer tape has no significant effects on the drag coefficient with or without turbulence grids. For the low turbulence intensity (without grid), the airfoil performance is improved when the boundary layer tape is attached near the leading edge. For the high turbulence intensity (with grid), in the case of the Re = 0.5 × 10 5, the pressure coefficient presents a steady value from some back positions of x/c = 0.20, where the boundary layer tape is attached on the trailing edge position. Highlights: Pressures are directly measured by multiport pressure devices in a static state. Static turbulence grids are used to adjust the turbulent intensity in wind tunnel. The tape significantly impacts the airfoil performance at Re ≥ 1.0 × 10 5 . Results are discussed at different turbulent intensities and low Reynolds numbers. For Re = 0.5 × 10 5, pressure coefficient shows a constant value from x/c = 0.20.